Enzymatically-synthesized xylo-oligosaccharides laurate esters as surfactants of interest. (September 2020) - Gérard, D.; Méline, T.; Muzard, M.; Deleu, M.; Plantier-Royon, R.; Rémond, C.
Abstract: Lipase-catalyzed synthesis of xylo-oligosaccharides esters from pure xylobiose, xylotriose and xylotetraose in the presence of vinyl laurate was investigated. The influence of different experimental parameters such as the loading of lipase, the reaction duration or the use of a co-solvent was studied and the reaction conditions were optimized with xylobiose. Under the best conditions, a regioselective esterification occurred to yield a monoester with the acyl chain at the OH-4 of the xylose unit at the non-reducing end. Surface-active properties of these pure xylo-oligosaccharides fatty esters have been evaluated. They display interesting surfactant activities that differ according to the degree of polymerization (DP) of the glycone moiety. Graphical abstract: Image 1 Highlights: Lipase N435 can catalyze acylation of xylo-oligosaccharides with vinyl laurate. Xylobiose, xylotriose and xylotetraose laurate monoesters are produced. Regioselective acylation at the OH-4 position of the non-reducing end xylose unit. Acylation yields decrease with the degree of polymerization of xylo-oligosaccharides. Degree of polymerization of the glycone moiety impacts the surfactant activities.